Popliteal artery cannulation as a saviour during prone positioning. Issue 6 (7th June 2020) - Bala, Narayan; Pathak, Vinay; Goyal, Shilpa; Kothari, Nikhil
Abstract : The cannulation of the peripheral artery is a prerequisite for invasive blood pressure monitoring and repeated arterial blood gas sampling. Radial artery is commonly used site for inserting an arterial cannula. Many times, either during the change of posture or during prone ventilation, the arterial cannula gets displaced, and it is challenging to reinsert the arterial cannula in the lateral or prone position. In such circumstances, an alternative site of arterial cannulation needs to be looked into; we report a case in which the popliteal artery was used for arterial cannulation while the patient was in a prone position.